System automation facilitating New Product Initiation (NPI) -journey towards modern trade & agile TM&D - Naieem, Ahmed Omar (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.